La historia del Límite para promover el conocimiento del contenido en los profesores - Rendón Mayorga, Cesar Guillermo (2022)
Some tasks about the concept of limit are presented, inspired by the History of Mathematics (HM) and addressed to teachers in initial training, in order to inquire about their relevance in the promotion of the content knowledge that the teacher should have. The proposal is based, on the one hand, on the usefulness that the use of the HM can have in teacher education (Furinghetti, 2007) and, on the other hand, on the work of Ball, Thames, and Phelps (2008), particularly on what they call "Specialized Content Knowledge". We show some results of the implementation of the tasks and an analysis of the reasoning put into play by the trainee teachers when solving them.